Efforts to increase agility and cooperation through traditional games in grade 5 SDN 20 Sitiung: Upaya meningkatkan Kelincahan dan kerjasama Melalui Permainan Tradisional di Kelas 5 SDN 20 Sitiung - rena dewita (International Journal of Technology Vocational Education and Training, 2020)
Research on the ability of this collaboration has gone through the instrument validation process in order to obtain the validity and reliability of the research instrument. The data analysis techniques used are descriptive qualitative and quantitative descriptive. This classroom action research aims to improve children's cooperation skills through dragon snake game activities in grade 5 SDN 20 Sitiung. The dragon game used is limited to the Dragon Snake game. The type of research used is classroom action with the subject of 20 students in grade 5 SDN 20 Sitiung. The data collection method used was the observation method and the documentation method. Through this activity, children's gross motor skills will be obtained on the learning abilities of students. Games that prioritize cognitive and affective will affect learning activities as well as agility and collaboration between student A and student B who play an active role in improving a good approach.